The Relationship of Husband Role on Psychological Adaptation Levels of Postpartum Mother in Camar1 Arifin Achmad Hospital Riau Province - Puswati, D; Suci, A (KnE Life Sciences, 2019)
Postpartum psychological adaptation is a mental process which is related to selfadjustment of a person after childbirth. One of the psychological factors that can increase the risk of postpartum depression is the lack of support or the husband’s role towards the wife. The pressure felt by postpartum mothers can cause the mother to experience stress. The purpose of the study was to determined husband role relationship on psychological adaptation levels of postpartum mother in Camar 1 Arifin Achmad Hospital Riau Province. The study used a quantitative research with correlation design of cross sectional approach. The research instrument has been tested for validity and reliability in Petalabumi Hospital with r alpha 0.873, and psychological adaptation instruments with r alpha 0.930. The population was 49 postpartum mothers, 22 respondents were sampled with accidental sampling technique. This study began from July 14th until July 21th 2018. The analysis used in this study was Chi-Square test. The result of the study is that the value = 0.011 <0.05, so Ho is rejected. It can be concluded that there is a significant relationship between the role of the husband to the level of psychological adaptation of postpartum mothers in Camar 1 RSUD Arifin Achmad Riau Province. Keywords: post-partum, psychological adaptation, the role of husband.